Pengaruh ESG Risk, Profitabilitas, dan Likuiditas terhadap Nilai Perusahaan - Alifah, Suciningtyas Nur; Ihsan, Dwi Nur'aini (Faculty of Economics and Business, 2025)
Environmental, Social, and Governance (ESG) has garnered attention from all levels of society in line with the increasing trend of sustainability. In efforts to enhance corporate reputation ESG as non-financial factors and financial factors, such as profitability and liquidity, are aspects that can influence firm value. This study aims to analyze the effect of ESG risk scores, profitability (ROE), and liquidity (CR) on firm value (Tobin's Q) among companies included in the Jakarta Islamic Index 70 (JII 70). The study's objects consist of 10 sharia-based companies with ESG risk scores from Sustainalytics categorized as negligible, low, or moderate risk during the 2020-2023 period. The analytical method used is panel data regression with Eviews 12. The results show that firm value is significantly influenced by profitability, while ESG risk and liquidity have no significant effect. However, ESG risk, profitability, and liquidity simultaneously and significantly influence firm value.